Cloning and sequence analysis of myogenin gene in wild boar - XU Huai-liang; YAO Yong-fang; ZHU Qing; PAN Yang (浙江大学学报. 农业与生命科学版)
Based on myogenin (MyoG) gene sequence of domesticated pig (X89007), two pairs of primer were designed and used to amplify an approximate 1.6 kb and 1.0 kb DNA fragment by PCR technique from genomic DNA sample of wild boar. The PCR products were ligated into the pMD-18T vector, and then transformed into competent cells of E. coli DH5a. The DNA sequencing and combining result showed that the MyoG gene of wild boar was 2 466 bp (without primer sequence) in length and contained three complete exons and two introns. The homology analysis of the MyoG gene sequences by Clustal W software indicated that, compared with domesticated pig, cattle, horse, dog, mouse and human, the cDNA sequence homologies of MyoG gene of wild boar were 99.8%, 92.4%, 92.7%, 89.7%, 90.8%, 94.0%, respectively, and the homologies of amino acid sequence were 100%, 96.4%, 95.9%, 94.1%, 96.4%, 96.8%, respectively. In addition, a total of 16 nucleotide variable sites were found and five sites of which were specific to wild boar. Most of variable sites occurred in the introns, especially the first intron. Theses results demonstrated that all exons of MyoG gene were highly conservative, but its introns (especially intron 1) were more polymorphic in the process of wild boar evolution. Screened with 117 enzymes, 78 recognition sites were found, and five positions of them included the variable sites. Especially, SmaI (CCC/GGG) or XmaI(C/CCGGG) recognition sites at site 1 153 with T being mutated into G was specific in the wild boar. DNA sequences were deposited to GenBank, and obtained sequence No. was FJ356697.